Computational fluid dynamics comparison of the upper airway velocity, pressure, and resistance in cats using an endotracheal tube or a supraglottic airway device - Zamora-Perarnau, Carla; Malvè, Mauro; Fernández-Parra, Rocío (Frontiers in Veterinary Science, 2023)
Intoduction In veterinary medicine, airway management of cats under general anesthesia is performed with an endotracheal tube (ETT) or supraglottic airway device (SGAD). This study aims to describe the use of computational fluid dynamics (CFD) to assess the velocities, pressures, and resistances of cats with ETT or SGAD. Methods A geometrical reconstruction model of the device, trachea, and lobar bronchi was carried out from computed tomography (CT) scans that include the head, neck, and thorax. Twenty CT scans of cats under general anesthesia using ETT (n = 10) and SGAD (n = 10) were modeled and analyzed. An inspiratory flow of 2.4 L/min was imposed in each model and velocity (m/s), general and regional pressures (cmH2O) were computed. General resistance (cmH2O/L/min) was calculated using differential pressure differences between the device inlet and lobar bronchi. Additionally, regional resistances were calculated at the device’s connection with the breathing circuit (region A), at the glottis area for the SGAD, and the area of the ETT exit (bevel) (region B) and the device itself (region C). Results Recirculatory flow and high velocities were found at the ETT’s bevel and at the glottis level in the SGAD group. The pressure gradient (Δp) was more enhanced in the ETT cases compared with the SGAD cases, where the pressure change was drastic. In region A, the Δp was higher in the ETT group, while in regions B and C, it was higher in the SGAD group. The general resistance was not statistically significant between groups (p = 0.48). Higher resistances were found at the region A (p = <0.001) in the ETT group. In contrast, the resistance was higher in the SGAD cases at the region B (p = 0.001). Discussion Overall, the provided CT-based CFD analysis demonstrated regional changes in airway pressure and resistance between ETT and SGAD during anesthetic flow conditions. Correct selection of the airway device size is recommended to avoid upper airway obstruction or changes in flow parameters.